Heat-conducting film as well as preparation method and application thereof
By modifying the sheet-shaped thermally conductive material with hydrophilic and hydrophobic compounds, a horizontally oriented thermally conductive film is solved, and the problems of high thermal conductivity and electrical insulation in the prior art are achieved, efficient heat dissipation and flexibility are achieved, and suitable for electronic components. .
Patent Information
- Application Number
- CN202411557609.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
Existing high-performance thermal interface materials are difficult to combine high thermal conductivity and good electrical insulation performance, especially in electronic packaging, light emitting diodes and aerospace fields, with urgent demand for heat dissipation.
Modify the sheet-shaped thermally conductive material by using a modified liquid. Through the modification of hydrophilic and hydrophobic compounds, a two-dimensional sheet-shaped thermally conductive film with horizontal orientation is formed, and the coating is combined with the binder aqueous solution to ensure that the thermally conductive material is in the microscopic shape. It forms a good thermal conductivity path in appearance and has both electrical insulation properties.
A high-oriented thermal conduction film with excellent thermal conduction performance was prepared under low thermal conduction amounts, which had high electrical insulation performance and flexibility, improved heat dissipation efficiency, and was simple in preparation, short time, low cost and environmentally friendly.
Smart Images

Figure CN119264486A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal conductive films, and in particular to a thermal conductive film and a preparation method and application thereof. Background Art
[0002] With the rapid development of communication technology and electronic technology, heat dissipation has become a research hotspot in the fields of integrated electronic packaging, light-emitting diodes, energy storage, and aerospace. In this context, high-performance thermal interface materials have received extensive attention. In addition to high thermal conductivity requirements, such materials usually also need to have good electrical insulation and mechanical properties. However, current high-performance thermal interface materials often find it difficult to have both high thermal conductivity and good electrical insulation.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a thermally conductive film and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0005] The present invention can be implemented like this:
[0006] In a first aspect, the present invention provides a method for preparing a thermally conductive film, comprising the following steps:
[0007] The sheet-like thermal conductive material is modified with a modifying liquid to obtain a modified thermal conductive material nanosheet; the modifying liquid includes a hydrophilic compound solution and a hydrophobic compound solution, and the mass ratio of the hydrophilic compound to the hydrophobic compound contained in the modifying liquid is (0.8-1):(0.8-1);
[0008] The modified thermal conductive material nanosheets are mixed with a binder aqueous solution, and an intermediate solution is obtained after removing part of the water; the intermediate solution is coated on the surface of a substrate with an oil agent, and the remaining solvent is removed to obtain a two-dimensional sheet-like thermal conductive film with a horizontal orientation.
[0009] In an optional embodiment, in the hydrophilic compound solution, the concentration of the hydrophilic compound is 0.5 mg / mL to 1.5 mg / mL;
[0010] And / or, in the hydrophobic compound solution, the concentration of the hydrophobic compound is 1.5 mg / mL to 2.5 mg / mL.
[0011] In an alternative embodiment, the hydrophilic compound comprises an alkylbenzene sulfonate having 10 to 14 carbon atoms;
[0012] And / or, the solvent of the hydrophilic compound solution is water.
[0013] In an alternative embodiment, the hydrophobic compound comprises an alkylamine having 6 to 18 carbon atoms;
[0014] And / or, the solvent of the hydrophobic compound solution includes ethanol.
[0015] In an alternative embodiment, the hydrophobic compound includes at least one of a dodecylamine chain, a hexadecylamine chain, and an octadecylamine chain.
[0016] In an optional embodiment, the modification includes at least one of the following features:
[0017] Feature 1: The mass ratio of the modified liquid to the sheet thermal conductive material is 100:10 to 100:50;
[0018] Feature 2: The modification is carried out at 500 rpm to 2500 rpm and 50° C. to 100° C. for 20 min to 120 min.
[0019] In an optional embodiment, the preparation of the sheet-like thermal conductive material includes: ball-milling a mixture of the thermal conductive material and sucrose; subsequently filtering and washing away the sucrose; dispersing the filter cake obtained by filtration in water and treating it in an ultrasonic cleaner for at least 1 hour, allowing it to stand, centrifuging the supernatant after standing, and drying the precipitate obtained by centrifugation to obtain the sheet-like thermal conductive material.
[0020] In an optional embodiment, the thermally conductive material includes at least one of boron nitride, aluminum oxide, aluminum nitride, silicon carbide, graphite, and graphene.
[0021] In an optional embodiment, the mass ratio of the thermally conductive material to sucrose is 1:4 to 1:6.
[0022] In an optional embodiment, the grinding balls used for ball milling are zirconium oxide with a diameter of 8 mm to 12 mm.
[0023] In an optional embodiment, the ball milling time is 4 hours to 12 hours.
[0024] In an optional embodiment, the standing time is 6 hours to 12 hours.
[0025] In an optional embodiment, the drying temperature is 60°C to 90°C.
[0026] In an optional embodiment, the mass ratio of the modified thermal conductive material nanosheets to the binder aqueous solution is 10:100 to 40:100.
[0027] In an alternative embodiment, the aqueous binder solution includes an aqueous PVA solution (polyvinyl alcohol aqueous solution).
[0028] In an optional embodiment, the PVA aqueous solution is obtained by mixing polyvinyl alcohol and water and then swelling them.
[0029] In an optional embodiment, the concentration of polyvinyl alcohol in the PVA aqueous solution is 4 mg / mL to 6 mg / mL.
[0030] In an optional embodiment, the swelling temperature is 85° C. to 95° C., and the swelling time is 1.5 h to 2.5 h.
[0031] In an optional embodiment, the viscosity of the intermediate solution is 500 mPa·s to 2000 mPa·s.
[0032] In a second aspect, the present invention provides a thermally conductive film, which is prepared by the preparation method of any one of the aforementioned embodiments.
[0033] In a third aspect, the present invention provides an electronic component, comprising the thermally conductive film of the aforementioned embodiment.
[0034] The beneficial effects of the present invention include:
[0035] The present application uses a modified liquid containing a hydrophobic compound and a hydrophilic compound to modify the amphiphilicity of the sheet-like thermal conductive material. After the surface of the sheet-like thermal conductive material is modified by amphiphilic molecules, there will be a certain attraction between the sheet-like thermal conductive materials with the same functional group during molding. The thermal conductive material will not have two pieces of material vertically distributed in the microscopic morphology, thereby forming a good thermal conductive path, and the sheet-like thermal conductive material can have a certain adsorption force with both oil and water when forming a film, so that the bottom layer of the thermal conductive material nanosheet has a horizontal orientation, and when the solvent is evaporated on the surface of the substrate coated with the oil agent, the material as a whole can form a certain horizontal orientation. This method can prepare a high-taken thermal conductive film with good thermal conductivity at a low amount of thermal conductive material. The preparation method is short in time, simple to operate, low in cost, and environmentally friendly. The prepared thermal conductive film can have both high electrical insulation performance and thermal conductivity. In addition, the thermal conductive film also has good flexibility. The above-mentioned thermal conductive film is used to prepare electronic components, which is conducive to improving the heat dissipation efficiency of the thermal conductive film. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0037] Figure 1 This is a SEM image of the thermally conductive film prepared in Example 1 of the present application at a first viewing angle;
[0038] Figure 2 This is a SEM image of the thermally conductive film prepared in Comparative Example 1 of the present application at a second viewing angle. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0040] The thermal conductive film provided by the present invention and its preparation method and application are described in detail below.
[0041] The present invention provides a method for preparing a thermally conductive film, which comprises the following steps:
[0042] S1: modifying a sheet-like thermal conductive material with a modifying liquid to obtain a modified thermal conductive material nanosheet; the modifying liquid includes a hydrophilic compound solution and a hydrophobic compound solution, and the mass ratio of the hydrophilic compound to the hydrophobic compound contained in the modifying liquid is (0.8-1):(0.8-1).
[0043] In some optional embodiments, the mass ratio of the hydrophilic compound to the hydrophobic compound in the modified liquid can be 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1:0.95, 1:0.9, 1:0.85 or 1:0.8, etc., or other values within the range of (0.8-1):(0.8-1). In some preferred embodiments, the mass ratio of the hydrophilic compound to the hydrophobic compound in the modified liquid is 1:1.
[0044] It should be noted that if the hydrophilic compound contained in the modified liquid is too little (such as the mass ratio of hydrophilic compound to hydrophobic compound is 0.5:1), it is easy to cause the hydrophobicity of the modified thermally conductive material to be too strong, the combination of the thermally conductive material and the PVA aqueous solution is not sufficient, and the thermally conductive filler in the film after molding is insufficient, which reduces the thermal conductivity of the prepared film; if the hydrophilic compound contained in the modified liquid is too much (such as the mass ratio of hydrophilic compound to hydrophobic compound is 1:1.5), it is easy to enhance the interaction between the modified thermally conductive material and the PVA aqueous solution, causing the dispersion of the material in the aqueous solution to deteriorate. This excessive hydrophilicity may cause the thermally conductive filler to re-aggregate during the molding process, reduce the effective thermal conductivity path in the film, and thus affect the thermal conductivity of the film. By controlling the mass ratio of the hydrophilic compound and the hydrophobic compound in the modified liquid within the scope of this application, the sheet-like thermally conductive material can be well modified, which is more conducive to obtaining a two-dimensional sheet-like thermally conductive film with a horizontal orientation.
[0045] Optionally, in the above-mentioned hydrophilic compound solution, the concentration of the hydrophilic compound can be 0.5 mg / mL to 1.5 mg / mL, such as 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL or 1.5 mg / mL, etc., or it can be other values within the range of 0.5 mg / mL to 1.5 mg / mL.
[0046] In the above-mentioned hydrophobic compound solution, the concentration of the hydrophobic compound can be 1.5 mg / mL to 2.5 mg / mL, such as 1.5 mg / mL, 1.6 mg / mL, 1.7 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2.0 mg / mL, 2.1 mg / mL, 2.2 mg / mL, 2.3 mg / mL, 2.4 mg / mL or 2.5 mg / mL, or other values within the range of 1.5 mg / mL to 2.5 mg / mL.
[0047] The volume ratio of the hydrophilic compound solution to the hydrophobic compound solution can be calculated based on the preset mass ratio of the hydrophilic compound to the hydrophobic compound in the modified solution and the concentration of the hydrophilic compound in the hydrophilic compound solution or the concentration of the hydrophobic compound in the hydrophobic compound solution.
[0048] In some optional embodiments, the hydrophilic compound includes an alkylbenzene sulfonate having a carbon number of 10 to 14 (such as 10, 11, 12, 13 or 14). Exemplarily, the hydrophilic compound can be a sodium salt of an alkylbenzene sulfonate having the above carbon number. The solvent of the hydrophilic compound solution is water.
[0049] The hydrophobic compound includes an alkylamine having a carbon number of 6 to 18 (6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18). Exemplarily, the hydrophobic compound may include at least one of a dodecylamine chain, a hexadecylamine chain and an octadecylamine chain. The hydrophobic compound has a longer carbon chain and can maintain sufficient hydrophobicity. In addition, the cost of the hydrophobic compound is low and grafting is easier. The solvent of the hydrophobic compound solution may include ethanol.
[0050] In some optional embodiments, the preparation of the sheet-like thermal conductive material includes: ball-milling a mixture of the thermal conductive material and sucrose; then filtering and washing away the sucrose; dispersing the filter cake obtained by filtration in water and treating it in an ultrasonic cleaner for at least 1 hour, allowing it to stand, centrifuging the supernatant after standing, and drying the precipitate obtained by centrifugation to obtain the sheet-like thermal conductive material.
[0051] The thermally conductive material may illustratively but not limitatively include at least one of boron nitride, aluminum oxide, aluminum nitride, silicon carbide, graphite and graphene.
[0052] The mass ratio of the thermal conductive material to sucrose may be 1:4 to 1:6, such as 1:4, 1:4.5, 1:5, 1:5.5 or 1:6, or other values within the range of 1:4 to 1:6.
[0053] The grinding balls used for ball milling can be zirconium oxide with a diameter of 8 mm to 12 mm (such as 8 mm, 9 mm, 10 mm, 11 mm or 12 mm, etc.).
[0054] The ball milling time can be 4 h to 12 h, such as 4 h, 6 h, 8 h, 10 h or 12 h, etc., or other values within the range of 4 h to 12 h.
[0055] The standing time may be 6 h to 12 h, such as 6 h, 8 h, 10 h or 12 h, etc., or may be other values within the range of 6 h to 12 h.
[0056] The centrifugation operation can be performed at a rotation speed of 5000 rpm for 5 minutes, and then the supernatant is processed at 8000 rpm for 10 minutes. The above centrifugation operation is repeated 2 to 3 times.
[0057] It should be noted that the powdered thermal conductive material can be peeled off into a sheet-like shape under the action of a ball mill and an ultrasonic cleaner.
[0058] In some embodiments, the mass ratio of the modified liquid to the sheet thermal conductive material can be 100:10 to 100:50, such as 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45 or 100:50, or other values within the range of 100:10 to 100:50.
[0059] If the mass ratio of the modified liquid to the sheet-like thermally conductive material is lower than 100:10 (such as 100:5), it is not conducive to the modification of the hydrophilicity and hydrophobicity of the thermally conductive material. Insufficient modification results in poor orientation of the prepared material and poor thermal conductivity. If the mass ratio of the modified liquid to the sheet-like thermally conductive material is higher than 100:50 (such as 100:60), it is not conducive to the formation of an excellent thermal conductive path between the thermally conductive filler and the binder, which will cause agglomeration between the sheets and poor thermal conductivity.
[0060] The modification can be carried out at 500rpm-2500rpm (such as 500rpm, 800rpm, 1000rpm, 1200rpm, 1500rpm, 1800rpm, 2000rpm, 2200rpm or 2500rpm, etc.), 50℃-100℃ (such as 50℃, 60℃, 70℃, 80℃, 90℃ or 100℃, etc.), for 20min-120min (such as 20min, 30min, 40min, 50min, 60min, 80min, 100min or 120min, etc.).
[0061] In some practical operations, the modified liquid can be mixed with the sheet-like thermal conductive material, stirred at 500 rpm to 2500 rpm and 50°C to 100°C for 20 min to 120 min to obtain a hydrophobic material-sheet-like thermal conductive material-hydrophilic material dispersion. Further, the hydrophobic material-sheet-like thermal conductive material-hydrophilic material dispersion is centrifuged (for example, it can be centrifuged at 8000 rpm for 10 min), and the above centrifugation operation is repeated 2 to 3 times. The bottom precipitate obtained after the final centrifugal washing is dried (such as dried in an oven at 80°C for 24 hours) to obtain a modified thermal conductive material nanosheet.
[0062] As mentioned above, by grafting hydrophobic compounds and hydrophilic compounds on both sides of the surface of the sheet-like thermal conductive material, the modified thermal conductive material nanosheets exhibit excellent interfacial activity and wettability, and the obtained thermal conductive film has a certain horizontal orientation and excellent thermal conductivity.
[0063] It should be noted that if the hydrophobic compound solution is first used to hydrophobically modify the sheet thermal conductive material, and then the hydrophilic compound solution is used to hydrophilically modify the sheet thermal conductive material; or if the hydrophilic compound solution is first used to hydrophilically modify the sheet thermal conductive material, and then the hydrophobic compound solution is used to hydrophobically modify the sheet thermal conductive material, the first modified group will be replaced by the later modified group, and the modification effect will be poor. In the present application, the hydrophobic compound solution and the hydrophilic compound solution are first mixed to prepare a modified solution, and then the sheet thermal conductive material is hydrophilically and hydrophobically modified at the same time, which can avoid the first modified group being replaced by the later modified group.
[0064] S2: Mix the modified thermal conductive material nanosheets with the binder aqueous solution, remove part of the water to obtain an intermediate solution; apply the intermediate solution to the surface of the substrate with an oil agent, remove the remaining solvent, and obtain a two-dimensional sheet-like thermal conductive film with a horizontal orientation.
[0065] In some optional embodiments, the mass ratio of the modified thermal conductive material nanosheets to the binder aqueous solution can be 10:100 to 40:100, such as 10:100, 15:100, 20:100, 25:100, 30:100, 35:100 or 50:100, or other values within the range of 10:100 to 40:100.
[0066] The binder aqueous solution includes a PVA aqueous solution, that is, the binder includes polyvinyl alcohol.
[0067] Optionally, the PVA aqueous solution can be obtained by mixing polyvinyl alcohol and water and then swelling them.
[0068] The concentration of polyvinyl alcohol in the above-mentioned PVA aqueous solution can be 4 mg / mL to 6 mg / mL, such as 4 mg / mL, 4.5 mg / mL, 5 mg / mL, 5.5 mg / mL or 6 mg / mL, or it can be other values within the range of 4 mg / mL to 6 mg / mL.
[0069] The swelling temperature may be 85°C to 95°C, such as 85°C, 88°C, 90°C, 92°C or 95°C, etc., or other values within the range of 85°C to 95°C.
[0070] The swelling time may be 1.5 h to 2.5 h, such as 1.5 h, 1.8 h, 2.0 h, 2.2 h or 2.5 h, etc., or other values within the range of 1.5 h to 2.5 h.
[0071] The modified thermal conductive material nanosheets and the binder aqueous solution can be mixed at 90° C. for 2 hours. By mixing the modified thermal conductive material nanosheets and the binder aqueous solution, the mixed solution of the two has a certain viscosity.
[0072] In some optional embodiments, part of the water may be removed by evaporation. The viscosity of the intermediate solution obtained by removing part of the water may be 500 mPa·s to 2000 mPa·s.
[0073] In some optional embodiments, the substrate may be a glass plate, and the oil agent on the surface of the substrate may be silicone oil.
[0074] In some optional embodiments, the remaining solvent can be removed at 60°C to 80°C (such as 60°C, 65°C, 70°C, 75°C or 80°C, etc.) for 2h to 4h (such as 2h, 2.5h, 3h, 3.5h or 4h, etc.), and then dried at 80°C to 90°C for 10h to 12h.
[0075] The present application utilizes a modification liquid containing a hydrophobic compound and a hydrophilic compound to perform amphiphilic modification on a sheet-like thermally conductive material. After the surface of the sheet-like thermally conductive material is modified by the amphiphilic molecules, there will be a certain attraction between the sheet-like thermally conductive materials with the same functional groups during molding, and the thermally conductive material will not have two sheets of material vertically distributed in the microscopic morphology, thereby forming a good thermal conductive path. In addition, when the sheet-like thermally conductive material forms a thin film, it can have a certain adsorption force with both oil and water, so that the bottom layer of the thermally conductive material nanosheet has a horizontal orientation. When the solvent is evaporated on the surface of the substrate coated with the oil agent, the material as a whole can form a certain horizontal orientation.
[0076] As mentioned above, the present application adopts a specific preparation method to modify the thermal conductive material, and the modified material has hydrophilic and hydrophobic properties, which is conducive to directional arrangement and horizontal orientation. The method can prepare a high-quality thermal conductive film with good thermal conductivity at a low thermal conductive material dosage. The preparation method is time-consuming, simple to operate, low-cost, and environmentally friendly.
[0077] Correspondingly, the present invention also provides a thermally conductive film, which is prepared by the above preparation method.
[0078] The thermally conductive film can have both high electrical insulation performance and thermal conductivity. In addition, the thermally conductive film also has good flexibility.
[0079] It should be noted that, taking hexagonal boron nitride (h-BN) as an example of a thermal conductive material, the thermal conductivity of the material is closely related to its orientation. At present, the commonly used methods for changing the orientation of hexagonal boron nitride include: electric field method, magnetic field method, template method and 3D printing method, but the above methods are cumbersome and costly, and the orientation of the resulting boron nitride film is not sufficient to have high electrical insulation and high thermal conductivity at the same time.
[0080] In addition, the present invention also provides an electronic component, which includes the above-mentioned thermal conductive film.
[0081] The heat-conductive film can have higher heat dissipation efficiency.
[0082] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0083] Example 1
[0084] This embodiment provides a thermally conductive film, and a preparation method thereof includes:
[0085] S1: Preparation of modified thermal conductive material nanosheets.
[0086] S11: Take 10g of hexagonal boron nitride powder and 50g of sucrose, mix them, and perform ball milling in a ball mill for 8h (the grinding beads are zirconium oxide with a diameter of 10mm) to obtain ball mill material; then filter and wash away the sucrose (wash with water), disperse the filter cake obtained by filtration in water and treat it in an ultrasonic cleaner for 1h, take it out and let it stand for 8h, and collect the supernatant.
[0087] S12: The supernatant is centrifuged at 500 rpm for 5 minutes, and then the supernatant is centrifuged again at 8000 rpm for 10 minutes. The centrifugation operation is repeated twice, and the bottom precipitate obtained by the final centrifugation is dried in an oven at 60° C. for 24 hours to obtain a sheet-shaped thermal conductive material.
[0088] S13: Take 0.2g of octadecylamine solution and dissolve it in 100mL of anhydrous ethanol to prepare an octadecylamine ethanol solution with a concentration of 2mg / mL. Dissolve 0.2g of sodium dodecylbenzene sulfonate in 200mL of deionized water to prepare a sodium dodecylbenzene sulfonate solution with a concentration of 1mg / mL. Mix 200mL of sodium dodecylbenzene sulfonate solution and 100mL of octadecylamine ethanol solution to obtain a modified solution, in which the mass ratio of hydrophilic compound to hydrophobic compound contained in the modified solution is 1:1.
[0089] S14: According to the mass ratio of the modified liquid to the sheet-like thermal conductive material of 100:10, 1.5 g of the sheet-like thermal conductive material obtained in S12 was added to the modified liquid obtained in S13, and stirred at 1000 rpm and 50°C for 30 minutes to obtain an octadecylamine-boron nitride-sodium dodecylbenzene sulfonate dispersion. The dispersion was centrifuged at 8000 rpm for 10 minutes, and the above centrifugation operation was repeated twice. The bottom precipitate obtained after the final centrifugal washing was dried in an oven at 80°C for 24 hours to obtain a modified thermal conductive material nanosheet.
[0090] S2: Preparation of a two-dimensional sheet-like thermally conductive film with horizontal orientation.
[0091] S21: Take 0.5 g of PVA and put it into a round-bottom flask, add 100 mL of deionized water, and swell it at 90° C. for 2 h under magnetic stirring to obtain a PVA aqueous solution with a concentration of 5 mg / mL.
[0092] S22: The modified thermal conductive material nanosheets obtained in S14 were added to the PVA aqueous solution obtained in S21 at a mass ratio of 10:100, and the mixture was evenly mixed, and then stirred at 90° C. for 2 h to obtain an intermediate solution with a viscosity of 869 mPa·s.
[0093] S23: coating the intermediate solution on a glass plate coated with silicone oil, evaporating the solvent at 70° C. for 3 h to obtain a thin film; and drying the thin film in an oven at 80° C. for 12 h to obtain a thermally conductive film.
[0094] Example 2
[0095] The difference between this embodiment and embodiment 1 is that the thermal conductive material is replaced by aluminum oxide.
[0096] Example 3
[0097] The difference between this embodiment and embodiment 1 is that the thermal conductive material is replaced by aluminum nitride.
[0098] Example 4
[0099] This embodiment provides a thermally conductive film, and a preparation method thereof includes:
[0100] S1: Preparation of modified thermal conductive material nanosheets.
[0101] S11: Take 10g of hexagonal boron nitride powder and 40g of sucrose, mix them, and perform ball milling in a ball mill for 4h (the grinding beads are zirconium oxide with a diameter of 8mm) to obtain a ball mill material; then filter and wash away the sucrose (wash with water), disperse the filter cake obtained by filtration in water and treat it in an ultrasonic cleaner for 2h, take it out and let it stand for 12h, and collect the supernatant.
[0102] S12: Centrifuge the supernatant at 500 rpm for 5 minutes, take the supernatant, and centrifuge the supernatant again at 8000 rpm for 10 minutes. Repeat the centrifugation operation for 3 times, and dry the bottom precipitate obtained by the final centrifugation in an oven at 60° C. for 24 hours to obtain a sheet-like thermal conductive material.
[0103] S13: 0.15 g of octadecylamine solution was dissolved in 100 mL of anhydrous ethanol to obtain an octadecylamine ethanol solution with a concentration of 1.5 mg / mL. 0.12 g of sodium dodecylbenzene sulfonate was dissolved in 240 mL of deionized water to obtain a sodium dodecylbenzene sulfonate solution with a concentration of 0.5 mg / mL. 240 mL of sodium dodecylbenzene sulfonate solution and 100 mL of octadecylamine ethanol solution were mixed to obtain a modified solution, wherein the mass ratio of the hydrophilic compound to the hydrophobic compound contained in the modified solution was 0.8:1.
[0104] S14: According to the mass ratio of the modified liquid to the sheet-like thermal conductive material of 100:10, 1.5 g of the sheet-like thermal conductive material obtained in S12 was added to the modified liquid obtained in S13, and stirred at 500 rpm and 70°C for 30 minutes to obtain an octadecylamine-boron nitride-sodium dodecylbenzene sulfonate dispersion. The dispersion was centrifuged at 8000 rpm for 10 minutes, and the above centrifugation operation was repeated 3 times. The bottom precipitate obtained by the final centrifugation was dried in an oven at 80°C for 24 hours to obtain a modified thermal conductive material nanosheet.
[0105] S2: Preparation of a two-dimensional sheet-like thermally conductive film with horizontal orientation.
[0106] S21: Take 0.4 g of PVA and put it into a round-bottom flask, add 100 mL of deionized water, and swell it at 90° C. for 2 h under magnetic stirring to obtain a PVA aqueous solution with a concentration of 4 mg / mL.
[0107] S22: The modified thermal conductive material nanosheets obtained in S14 were added to the PVA aqueous solution obtained in S21 at a mass ratio of 20:100, and the mixture was evenly mixed, and then stirred at 85° C. for 2.5 h to obtain an intermediate solution with a viscosity of 834 mPa·s.
[0108] S23: coating the intermediate solution on a glass plate coated with silicone oil, evaporating the solvent at 60° C. for 4 h to obtain a thin film; and drying the thin film in an oven at 85° C. for 10 h to obtain a thermally conductive film.
[0109] Example 5
[0110] This embodiment provides a thermally conductive film, and a preparation method thereof includes:
[0111] S1: Preparation of modified thermal conductive material nanosheets.
[0112] S11: Take 10g of hexagonal boron nitride powder and 60g of sucrose, mix them, and perform ball milling in a ball mill for 12h (the grinding beads are zirconium oxide with a diameter of 12mm) to obtain a ball mill material; then filter and wash away the sucrose (wash with water), disperse the filter cake obtained by filtration in water and treat it in an ultrasonic cleaner for 1.5h, take it out and let it stand for 6h, and collect the supernatant.
[0113] S12: Centrifuge the supernatant at 500 rpm for 5 minutes, take the supernatant, and centrifuge the supernatant again at 8000 rpm for 10 minutes. Repeat the centrifugation operation twice, and dry the bottom precipitate obtained by the final centrifugation in an oven at 60° C. for 24 hours to obtain a sheet-like thermal conductive material.
[0114] S13: 0.24 g of octadecylamine solution was dissolved in 100 mL of anhydrous ethanol to obtain an octadecylamine ethanol solution with a concentration of 2.4 mg / mL. 0.3 g of sodium dodecylbenzene sulfonate was dissolved in 200 mL of deionized water to obtain a sodium dodecylbenzene sulfonate solution with a concentration of 1.5 mg / mL. 200 mL of sodium dodecylbenzene sulfonate solution and 150 mL of octadecylamine ethanol solution were mixed to obtain a modified solution, in which the mass ratio of hydrophilic compounds to hydrophobic compounds contained in the modified solution was 1:1.2.
[0115] S14: According to the mass ratio of the modified liquid to the sheet-like thermal conductive material of 100:50, 1.5 g of the sheet-like thermal conductive material obtained in S12 was added to the modified liquid obtained in S13, and stirred at 1500 rpm and 100° C. for 120 min to obtain a dispersion of octadecylamine-boron nitride-sodium dodecylbenzene sulfonate. The dispersion was centrifuged at 8000 rpm for 10 min, and the above centrifugation operation was repeated twice. The bottom precipitate obtained by the final centrifugation was dried in an oven at 80° C. for 24 h to obtain a modified thermal conductive material nanosheet.
[0116] S2: Preparation of a two-dimensional sheet-like thermally conductive film with horizontal orientation.
[0117] S21: Take 0.6 g of PVA and put it into a round-bottom flask, add 100 mL of deionized water, and swell it at 90° C. for 2 h under magnetic stirring to obtain a PVA aqueous solution with a concentration of 6 mg / mL.
[0118] S22: The modified thermal conductive material nanosheets obtained in S14 were added to the PVA aqueous solution obtained in S21 at a mass ratio of 40:100, and the mixture was evenly mixed, and then stirred at 95° C. for 1.5 h to obtain an intermediate solution with a viscosity of 921 mPa·s.
[0119] S23: coating the intermediate solution on a glass plate coated with silicone oil, evaporating the solvent at 80° C. for 2 h to obtain a thin film; and drying the thin film in an oven at 90° C. for 11 h to obtain a thermally conductive film.
[0120] Comparative Example 1
[0121] This comparative example is compared with Example 1:
[0122] Steps S11 and S12 were not performed.
[0123] S13: Same as Example 1.
[0124] S14: Replace the sheet-shaped thermally conductive material in Example 1 with an equal amount of commercially available spherical boron nitride, and the remaining conditions are the same as in Example 1.
[0125] S2: Same as Example 1.
[0126] Comparative Example 2
[0127] This comparative example is compared with Example 2:
[0128] Steps S11 and S12 were not performed.
[0129] S13: Same as Example 2.
[0130] S14: Replace the sheet-like thermal conductive material in Example 2 with an equal amount of commercially available spherical alumina, and the other conditions are the same as Example 2.
[0131] S2: Same as Example 2.
[0132] Comparative Example 3
[0133] This comparative example is compared with Example 3:
[0134] Steps S11 and S12 were not performed.
[0135] S13: Same as Example 3.
[0136] S14: Replace the sheet-shaped thermal conductive material in Example 3 with an equal amount of commercially available spherical aluminum nitride, and the remaining conditions are the same as in Example 3.
[0137] S2: Same as Example 3.
[0138] Comparative Example 4
[0139] The difference between this comparative example and Example 1 is that the mass ratio of the hydrophilic compound to the hydrophobic compound contained in the modified liquid is 0.5:1.
[0140] Comparative Example 5
[0141] The difference between this comparative example and Example 1 is that the mass ratio of the hydrophilic compound to the hydrophobic compound contained in the modified liquid is 1:1.5.
[0142] Comparative Example 6
[0143] The difference between this comparative example and Example 1 is that the mass ratio of the modified liquid to the sheet-like thermal conductive material is 100:5.
[0144] Comparative Example 7
[0145] The difference between this comparative example and Example 1 is that the mass ratio of the modified liquid to the sheet-like thermal conductive material is 100:60.
[0146] Comparative Example 8
[0147] The difference between this comparative example and Example 1 is that the hydrophilicity of the sheet-shaped thermal conductive material is first modified by using a hydrophilic compound solution, and then the hydrophobicity of the sheet-shaped thermal conductive material is modified by using a hydrophobic compound solution.
[0148] Comparative Example 9
[0149] The difference between this comparative example and Example 1 is that the hydrophobicity of the sheet-shaped thermal conductive material is firstly modified by using a hydrophobic compound solution, and then the hydrophilicity of the sheet-shaped thermal conductive material is modified by using a hydrophilic compound solution.
[0150] Test example
[0151] ①. The structure of the thermally conductive film prepared in Example 1 was observed, and the results are as follows: Figure 1 and Figure 2 shown.
[0152] Depend on Figure 1 and Figure 2 It can be seen that the thermally conductive film prepared in Example 1 has obvious orientation.
[0153] ②. Comparison of thermal conductivity and electrical insulation properties of the thermally conductive films prepared in the above Examples 1 to 5 and Comparative Examples 1 to 9.
[0154] The thermal conductivity of the thermally conductive film is characterized by the thermal conductivity coefficient. Specifically, the in-plane thermal conductivity and out-of-plane thermal conductivity of each thermally conductive film are measured using a NETZSCH LFA467 flash thermal conductivity meter.
[0155] The electrical insulation is characterized by volume resistivity. Specifically, the volume resistivity of each thermal conductive film is measured using an AVIC Dingli LCJ-50E resistance tester.
[0156] The results are shown in Table 1.
[0157] Table 1 Test results
[0158] It can be seen from Examples 1 to 5 that by modifying the sheet-shaped thermally conductive material, the unique structure of these sheet-shaped materials allows the introduction of hydrophilic and hydrophobic groups on both sides thereof, and the modification is beneficial to improving the thermal conductivity of the material (especially the in-plane thermal conductivity). In contrast, the modification of Comparative Examples 1 to 3 using spherical materials did not achieve the same effect.
[0159] In addition, by comparing Example 1 and Comparative Examples 4 to 9, it can be seen that when the hydrophobic compound and the hydrophilic compound are improperly compounded, or the amounts of the modified liquid and the sheet-like thermal conductive material are improperly used, or the hydrophobic modification and the hydrophilic modification are performed in a certain order, the performance of the prepared thermal conductive film will be reduced, and it will be difficult to have both high thermal conductivity and electrical insulation.
[0160] In summary, the present application uses a modified liquid containing a hydrophobic compound and a hydrophilic compound to modify the amphiphilicity of the sheet-like thermal conductive material. After the surface of the sheet-like thermal conductive material is modified by amphiphilic molecules, there will be a certain attraction between the sheet-like thermal conductive materials with the same functional group during molding. The thermal conductive material will not have two pieces of material vertically distributed in the microscopic morphology, thereby forming a good thermal conductive path, and the sheet-like thermal conductive material can have a certain adsorption force with both oil and water when forming a film, so that the bottom layer of the thermal conductive material nanosheet has a horizontal orientation, and when the solvent is evaporated on the surface of the substrate coated with the oil agent, the material as a whole can form a certain horizontal orientation. This method can prepare a high-taken thermal conductive film with good thermal conductivity at a low amount of thermal conductive material. The preparation method is short in time, simple to operate, low in cost, and environmentally friendly. The prepared thermal conductive film can have both high electrical insulation performance and thermal conductivity. In addition, the thermal conductive film also has good flexibility. The above-mentioned thermal conductive film is used to prepare electronic components, which is conducive to improving the heat dissipation efficiency of the thermal conductive film.
[0161] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a thermally conductive film, characterized in that: The following steps are involved: The sheet-like thermal conductive material is modified with a modifying liquid to obtain a modified thermal conductive material nanosheet; the modifying liquid comprises a hydrophilic compound solution and a hydrophobic compound solution, and the mass ratio of the hydrophilic compound to the hydrophobic compound contained in the modifying liquid is (0.8-1):(0.8-1); The modified thermal conductive material nanosheet is mixed with a binder aqueous solution, and an intermediate solution is obtained after removing part of the water; the intermediate solution is coated on the surface of a substrate with an oil agent, and the remaining solvent is removed to obtain a two-dimensional sheet-like thermal conductive film with a horizontal orientation.
2. The preparation method according to claim 1, characterized in that: In the hydrophilic compound solution, the concentration of the hydrophilic compound is 0.5 mg / mL to 1.5 mg / mL; And / or, in the hydrophobic compound solution, the concentration of the hydrophobic compound is 1.5 mg / mL to 2.5 mg / mL.
3. The preparation method according to claim 2, characterized in that: The hydrophilic compound includes an alkylbenzene sulfonate having 10 to 14 carbon atoms; And / or, the solvent of the hydrophilic compound solution is water.
4. The preparation method according to claim 2, characterized in that: The hydrophobic compound includes an alkylamine having 6 to 18 carbon atoms; and / or, the solvent of the hydrophobic compound solution comprises ethanol; Preferably, the hydrophobic compound includes at least one of a dodecylamine chain, a hexadecylamine chain, and an octadecylamine chain.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The modification includes at least one of the following features: Feature 1: The mass ratio of the modified liquid to the sheet-shaped thermal conductive material is 100:10 to 100:50; Feature 2: The modification is carried out at 500 rpm to 2500 rpm and 50° C. to 100° C. for 20 min to 120 min.
6. The preparation method according to claim 1, characterized in that: The preparation of the sheet-shaped thermal conductive material comprises: ball-milling a mixture of the thermal conductive material and sucrose; then filtering and washing away the sucrose; dispersing the filter cake obtained by the filtration in water and treating it in an ultrasonic cleaner for at least 1 hour, standing, centrifuging the supernatant after standing, and drying the precipitate obtained by centrifugation to obtain the sheet-shaped thermal conductive material; Preferably, the thermally conductive material comprises at least one of boron nitride, aluminum oxide, aluminum nitride, silicon carbide, graphite and graphene; Preferably, the mass ratio of the thermally conductive material to the sucrose is 1:4 to 1:6; Preferably, the grinding balls used for ball milling are zirconium oxide with a diameter of 8 mm to 12 mm; Preferably, the ball milling time is 4 h to 12 h; Preferably, the standing time is 6h to 12h; Preferably, the drying temperature is 60°C to 90°C.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the modified thermal conductive material nanosheets to the binder aqueous solution is 10:100 to 40:100; Preferably, the binder aqueous solution comprises a PVA aqueous solution; Preferably, the PVA aqueous solution is obtained by mixing polyvinyl alcohol and water and then swelling them; Preferably, the concentration of polyvinyl alcohol in the PVA aqueous solution is 4 mg / mL to 6 mg / mL; Preferably, the swelling temperature is 85° C. to 95° C., and the swelling time is 1.5 h to 2.5 h.
8. The preparation method according to claim 1, characterized in that: The viscosity of the intermediate solution is 500 mPa·s to 2000 mPa·s.
9. A thermally conductive film, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. An electronic component, characterized in that: The electronic component comprises the thermally conductive film according to claim 9.